Degraded Land Restoration in Reinstating CH4 Sink - Singh, Jay Shankar; Gupta, Vijai K. (Frontiers in Microbiology, 2016)
Methane (CH4), a potent greenhouse gas, contributes about one third to the global green house gases emissions. CH4 assimilating microbes (mostly methanotrophs) in upland soils play very crucial role in mitigating the CH4 release to the atmosphere. Agricultural, environmental and climatic shifts can alter CH4 sink profiles of soils, likely through shifts in CH4 assimilating microbial community structure and function. Landuse change, as forest and grassland ecosystems altered to agro-ecosystems, has already attenuated the soil CH4 sink potential, and are expected to be continued in the future. We hypothesized that variations in CH4 uptake rates in soils under different landuse practices could be an indicative of alterations in the abundance and/or type of methanotrophic communities in such soils. However, only a few studies have addressed to number and methanotrophs diversity and their correlation with the CH4 sink potential in soils of rehabilitated/restored lands. We focus on landuse practices can potentially mitigate CH4 gas emissions, the most prominent of which are improved cropland, grazing land management, use of bio-fertilizers and restoration of degraded lands. In this perspective paper, it is proposed that restoration of degraded lands can contribute considerably to improved soil CH4 sink strength by retrieving/conserving abundance and assortment of efficient methanotrophic communities. We believe that this report can assist in identifying future experimental directions to the relationships between landuse changes, methane-assimilating microbial communities and soil CH4 sinks. The exploitation of microbial communities other than methanotrophs can contribute significantly to the global CH4 sink potential and can add value in